Cover Jurnal Fitopatologi Vol. 18 No. 5, September 2022 - Editors (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2022)
This editorial contains the front cover, editorial page, and back cover of the Jurnal Fitopatologi Indonesia Vol. 18 No. 5, September 2022